2006
DOI: 10.1002/uog.3251
|View full text |Cite
|
Sign up to set email alerts
|

OP09.08: Fetal soft tissue and birth weight: their relationship to newborn infant body composition

Abstract: A total of 602 organ systems in 260 exams out of 193 patients were identified for this study (26 exams in the first trimester, 161 in the second, and 73 in third trimester). Table 1 shows the total number of organs scanned with 3DUS for each impact group. In the D group, the most significant findings were in these organs: face exams 10, brain 5 and uterine shape 4. In the I group, the most significant findings were in these organs: extremities 16 exams, urogenital system 15, placenta 15 and brain 10. In the V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The significant correlation between the fractional limb volume and neonatal body fat is also consistent with the results of a study that used air displacement plethysmography to determine neonatal body composition. 19 The r 2 values for fractional thigh volume (0.55) and fractional arm volume (0.39) were similar to those identified in this study (0.54 and 0.39, respectively).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The significant correlation between the fractional limb volume and neonatal body fat is also consistent with the results of a study that used air displacement plethysmography to determine neonatal body composition. 19 The r 2 values for fractional thigh volume (0.55) and fractional arm volume (0.39) were similar to those identified in this study (0.54 and 0.39, respectively).…”
Section: Discussionsupporting
confidence: 84%
“…This finding corroborates those of a previous study of incorporation of the fractional fetal thigh volume into the estimation of fetal weight. 18,19 We found fetal weight estimates that included the fractional thigh volume to be more frequently within 15% of actual birth weights and to be consistently accurate across a wide range of birth weights compared with traditional 2D biometric measurements. A larger study may be necessary to corroborate this finding given the small subset of patients who had birth weights of less than 2500 g. We also observed that the fetal fractional thigh and upper arm volumes correlated significantly with neonatal skin fold measurements and markers of neonatal obesity.…”
Section: Discussionmentioning
confidence: 81%
“…So ssue was included to aid in the predic on of birth weight and to correlate the fetal limb fat volume with neonatal parameters of fat. It was found that es mated fetal weight from 2D biometric measurements and the frac onal thigh volume correlated with actual birth weight be er than es mated fetal weight collected on the basis of tradi onal biometric [15][16][17] measurements on 2D ultrasonography alone.…”
Section: Discussionmentioning
confidence: 94%